Pengembangan Permainan Monopoli Nutriventure Game Sebagai Upaya Stimulasi Pemahaman Gizi Seimbang Anak Usia 5-6 Tahun - Putri, Sintya Tiara; Pramono; Munaisra Tri Tirtaningsih (PG PAUD Universitas Negeri Surabaya, 2023)
Nutrition in early childhood is not only crucial for physical growth. Nutrition also influences cognitive development, socio-emotional development, and motor development. If a child does not have a balanced nutritional intake, their growth and development will be challenging to optimize. To provide an understanding of nutrition for children, a enjoyable approach is needed, such as through games. The objective of this research is to develop the Nutriventure Game Monopoly and assess its feasibility by experts. This study employs the Research and Development (R&D) method with the development model according to the Borg and Gall theory. Validation sheets from content experts, game experts, and user experts (teachers) are used as data collection instruments, which are then analyzed using a Likert scale. The small-scale trial in this research involved 8 children from kindergarten group B, while the large-scale trial involved 60 kindergarten group B children. The research results show that the Nutriventure Game Monopoly is highly suitable for use as a learning tool about child nutrition, as indicated by the percentage values of 90% by content experts, 90% by game experts, and 95% by user experts. According to the Likert scale, the average total percentage value from content experts, game experts, and user experts is 92%, where >80% ? 100%, indicating that the development of the Nutriventure Game Monopoly falls into the category of highly suitable.